Development finance companies: aspects of policy and operation - Diamond, William (Baltimore: Johns Hopkins Press, 1968)
This is a compendium of essays following the conference of Developing Finance Companies held in 1965. In place of proceedings, it is presented here an essay of each of the subjects discussed at the conference
Includes index
osc 28/01/2019
Loans
Keywords: Development Banks; Development finance